Особенности управления электромеханическими системами механизмов поворота - Герасимяк, Ростислав Павлович; Найденко, Елена Валерьевна (НТУ "ХПИ", 2010)
The dependence of dynamic coefficient at the moment of control action switching on the initial conditions has been examined. The possibility of its decrease is show.
Particularities of electromechanics system`s management of rotate mechanisms
Keywords: инерция; момент динамический; нагрузка; жесткость эквивалентная